Neuromuscular paralysis by the basic phospholipase A2 subunit of crotoxin from Crotalus durissus terrificus snake venom needs its acid chaperone to concurrently inhibit acetylcholine release and produce muscle blockage - Cavalcante, Walter L.G. [UNESP]; Noronha-Matos, José B.; Timóteo, Maria A.; Fontes, Marcos R.M. [UNESP]; Gallacci, Márcia [UNESP]; Correia-de-Sá, Paulo (Elsevier, 2017)
Background and purpose Crotoxin (CTX), a heterodimeric phospholipase A2 (PLA2) neurotoxin from Crotalus durissus terrificus snake venom, promotes irreversible blockade of neuromuscular transmission. Indirect electrophysiological evidence suggests that CTX exerts a primary inhibitory action on transmitter exocytosis, yet contribution of a postsynaptic action of the toxin resulting from nicotinic receptor desensitization cannot be excluded. Here, we examined the blocking effect of CTX on nerve-evoked transmitter release measured directly using radioisotope neurochemistry and video microscopy with the FM4-64 fluorescent dye. Experimental approach Experiments were conducted using mice phrenic-diaphragm preparations. Real-time fluorescence video microscopy and liquid scintillation spectrometry techniques were used to detect transmitter exocytosis and nerve-evoked [3H]-acetylcholine ([3H]ACh) release, respectively. Nerve-evoked myographic recordings were also carried out for comparison purposes. Key results Both CTX (5 μg/mL) and its basic PLA2 subunit (CB, 20 μg/mL) had biphasic effects on nerve-evoked transmitter exocytosis characterized by a transient initial facilitation followed by a sustained decay. CTX and CB reduced nerve-evoked [3H]ACh release by 60% and 69%, respectively, but only the heterodimer, CTX, decreased the amplitude of nerve-evoked muscle twitches. Conclusion and implications Data show that CTX exerts a presynaptic inhibitory action on ACh release that is highly dependent on its intrinsic PLA2 activity. Given the high safety margin of the neuromuscular transmission, one may argue that the presynaptic block caused by the toxin is not enough to produce muscle paralysis unless a concurrent postsynaptic inhibitory action is also exerted by the CTX heterodimer.
Keywords: Crotalinea Snake Venom; Crotalus durissus terrificus; Neuromuscular transmission; Phospholipase A2; Real-time transmitter exocytosis; [3H]-Acetylcholine Release